Experimental analysis of the effect of low water temperature on oogenesis of juvenile chum salmon - О. V. Zelennikov (Известия ТИНРО, 2024)
The state of gonads is examined for juvenile chum salmon exposed for two weeks at low water temperature, for different stages of their embryonic-larval development. The transfer of the embryos and larvae from the water with temperature of 10.0–12.0 о C to the water with temperature of 1.3–1.8 о C slowed both somatic growth of the fish and development of their germ cells in all cases. The deficit in body weight and ovarian weight of experimental fish was not compensated later. However, the gonad weight was decreased in the somatic component and did not affect the fund of germ cells, in the medium term. The state of ovaries did not differ between the control and experimental groups of fish 50 days after the end of exposure, regardless of the initial condition of gonads in the experiment.